HASIL PEMERIKSAAN SILINDER PADA SEDIMEN URINE PASIEN GAGAL GINJAL KRONIS - Arifin, Zainul; Sayekti, Sri; Meinawati, Lusianah; Putri, Afdhaliyah Ayu (Jurnal Borneo Cendekia, 2025)
Chronic Kidney Disease is an irreversible disease with abnormalities in structure and function of the kidneys. Chronic kidney disease was characterized by one or more signs of kidney damage, one of them is urinary sediment abnormalities. Casts are one of the organic elements in urine sediments. Waxy cast most commonly found in patients with severe chronic kidney disease. Another source said that hyaline cast will be found in high quantities in patients with chronic kidney disease. Lack of in-depth research, types and composition of cast in chronic kidney disease urine sediments still need to be explored further. The objective of this study was to assess the findings of cast examinations in the urine sediment of chronic kidney disease patients at Kediri District Hospital.of chronic kidney disease patients at RSUD Kabupaten Kediri. The type of research used descriptive. The sampling technique used purposive sampling. The design of research used a cross-sectional. The sample used 12 people. The variables researched were cast element in the urine sediment of chronic kidney disease patients at RSUD Kabupaten Kediri. The examination method was manually using a microscope. The result showed that most of the respondents found cast in urine sedimemt in the amount of 8 respondents (67%) and almost half of the respondents not found cast in the urine sediment in the amount of 4 respondents (33%). The most commonly types of cast were waxy cast and granular cast. The conclusion of the research was that most of the respondents found cast in urine sediment (abnormal). The most commonly types of cast were waxy cast and granular cast. The researcher's suggestion for respondents is to conduct urine sediment examination to evaluate kidney disease routinely every 3-6 months at least once.